2014
DOI: 10.4236/aim.2014.42012
|View full text |Cite
|
Sign up to set email alerts
|

Grape Phenolic Extract Potentially Useful in the Control of Antibiotic Resistant Strains of <i>Campylobacter</i>

Abstract: In this work, a grape phenolic extract obtained by methanol extraction has been demonstrated to be effective in inhibiting the growth of different strains and species of Campylobacter, one of the most important bacterial foodborne pathogens causing gastroenteritis worldwide. Noteworthily, it was particularly effective against several strains presenting multiple antibiotic resistances. In all cases, the minimum inhibitory concentration (MIC) was lower than 300 mg GAE/L, being of 60 mg GAE/L for one of the most … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
1

Year Published

2016
2016
2017
2017

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 33 publications
1
4
0
1
Order By: Relevance
“…Anthocyanins, phenolic acids and stilbenes were in minor proportion. Despite the effects of the fermentation and the mildest process used for phenolic extraction, the distributions in families of individual phenolic compounds were similar to those obtained from the GSE (Silvan et al, 2013) or grapes (Mingo et al, 2014). Also, in the WWE, t-resveratrol and t-piceid were found and quantified.…”
Section: Phenolic Characterization Of Wwesupporting
confidence: 67%
See 2 more Smart Citations
“…Anthocyanins, phenolic acids and stilbenes were in minor proportion. Despite the effects of the fermentation and the mildest process used for phenolic extraction, the distributions in families of individual phenolic compounds were similar to those obtained from the GSE (Silvan et al, 2013) or grapes (Mingo et al, 2014). Also, in the WWE, t-resveratrol and t-piceid were found and quantified.…”
Section: Phenolic Characterization Of Wwesupporting
confidence: 67%
“…In addition to being the major phenolic compounds constituting the extract, there are several reports describing the antibacterial effect of catechins and proanthocyanidins against different bacteria (Nakayama, Shimatani, Ozawa, Shigemune, Tsugukuni, Tomiyama, et al, 2013;Reygaert, 2014). Moreover, we have previously observed some antibacterial effect of pure epicatechin on C. jejuni (Ganan et al, 2009;Mingo et al, 2014). The fractioning of a commercial grape seed extract active against Campylobacter also suggested that some catechins were involved in the antibacterial effect of the whole extract (Silvan et al, 2013), however it was difficult to associate the effect to a specific compound or family of compounds, because three of the four obtained fractions had antibacterial activity against Campylobacter.…”
Section: Phenolic Characterization Of Wwementioning
confidence: 86%
See 1 more Smart Citation
“…The antibacterial activity of grape phenolics has been attributed to the antimicrobial effects on bacteriostatic actions through changes in cell morphology and DNA content (Paulo et al 2010). Additionally, resveratrol can be used to control Campylobacter and Arcobacter foodborne pathogens with antibacterial, antibiofilm and anti- QS potential activities, especially as inclusion complexes, which promote slower release of these compound within food and food products (Silv an et al 2013;Mingo et al 2014;Duarte et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The by-products of plant processing for food represent a major disposal problem, although some of these might be promising sources of compounds with favourable technological or nutritional properties (Davidson et al 2013;Teixeira et al 2014;Xu et al 2016). For the control of Campylobacter contamination, the potential for efficient and safe application of antimicrobial phytochemicals obtained from agro-food by-products means that it is important to study such bioactivities in vitro and in vivo (Silv an et al 2013;Mingo et al 2014).…”
Section: Introductionmentioning
confidence: 99%